2020
DOI: 10.2334/josnusd.19-0459
|View full text |Cite
|
Sign up to set email alerts
|

A perspective from experimental studies of burning mouth syndrome

Abstract: Burning mouth syndrome (BMS) is one of the most frequently seen idiopathic pain conditions in a dental setting. Peri-and postmenopausal women are most frequently affected, and patients who experience BMS complain of persistent burning pain mainly at the tip and the bilateral border of the tongue. Recent studies have assessed whether BMS is a neuropathic pain condition, based on morphologic changes in biopsied tongue specimens, and whether there are abnormal pain responses in patients with this disease. Somatos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 83 publications
1
13
0
Order By: Relevance
“…De Kruijf et al reported a significant association between years after menopause and cold and warmth sensitivity thresholds in patients with chronic pain [17]. In a previous study, we found an association between somatosensory dysfunction and disease duration in patients with BMS [14,18].…”
supporting
confidence: 48%
“…De Kruijf et al reported a significant association between years after menopause and cold and warmth sensitivity thresholds in patients with chronic pain [17]. In a previous study, we found an association between somatosensory dysfunction and disease duration in patients with BMS [14,18].…”
supporting
confidence: 48%
“…Patients with BMS often complain of pain when eating hot or spicy foods. 2 , 12 Quantitative sensory testing (QST) studies of the pain threshold of patients with BMS have had similar findings. Yilmaz et al.…”
Section: Introductionmentioning
confidence: 85%
“… 15 In a previous study, we found an association between somatosensory dysfunction and disease duration in patients with BMS. 12 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that BMS affects taste perception through the interaction between the affected sensory and nearby trigeminal taste fibers, suggesting that it is not exclusively a taste-related pathology. 32 Therefore, treating BMS is more similar to treating chronic pain disorders.…”
Section: Transduction Of Tastementioning
confidence: 99%